Reduced cyclin D3 expression in erythroid cells protects against malaria - Maria Giuseppina Marini; Maura Mingoia; Maristella Steri; Ioannis Tsamesidis; Maria Laura Idda; Alessia Manca; Cristina D’Avino; Francesca Virdis; Valeria Lodde; Antonella Mulas; Isadora Asunis; Xinyi Li; et al. (Nature, 2026)
Abstract The severity of malaria varies substantially between individuals, but the mechanisms that underlie these differences remain unclear. Because erythrocytes have a key role in malaria biology, genetic variants associated with the development of these cells could inform the mechanisms that determine disease severity. Here we investigate the mechanistic basis of the association of the variant rs112233623-T with erythrocyte properties, and examine its role in modulating malaria severity. This variant is associated with increased levels of haemoglobin A2, increased erythrocyte size and reduced erythrocyte number 1,2 . It is found in an erythroid enhancer of CCND3 , which encodes cyclin D3—a cell-division activator that enhances the pentose phosphate pathway and thereby helps to counteract reactive oxygen species (ROS) 3 . We show that rs112233623-T disrupts a binding site for the transcription factor SMAD3, weakens enhancer activity and, in erythrocyte precursors (erythroblasts), is associated with reduced CCND3 expression and inhibition of the G1–S cell-cycle transition, concomitant with a reduction in the number of erythrocytes and an increase in their size. Using population genetic methods, we observe signatures of positive selection for rs112233623-T in the genetic history of Sardinia, a region in which malaria was once prevalent. Furthermore, we show that parasite growth is impaired in cultured Plasmodium falciparum -infected erythrocytes from rs112233623-T carriers, and that this impairment correlates with ROS levels. This mirrors our observations in erythrocytes from individuals who are deficient in the pentose-phosphate-pathway enzyme G6PD—a trait associated with protection against malaria in some settings—and highlights a common ROS-based mechanism of malaria resistance. Our results suggest that a reduction in CCND3 in erythroblasts constitutes a mechanism of resistance to malaria, and could enable therapeutic interventions.